Delivery and assessment method of Bachelor of Chemical Engineering (Environment) Programme during the Covid-19 pandemic / Faraziehan Senusi, Siti Khatijah Jamaludin and Norhaslinda Nasuha - Senusi, Faraziehan; Jamaludin, Siti Khatijah; Nasuha, Norhaslinda (Universiti Teknologi MARA, 2021)
As the Coronavirus disease was declared by the World Health Organization, the Government of Malaysia enforced a Movement Control Order (MCO) starting on March 18, 2020 to break the chain of Covid-19. Educational institutions including schools and higher education have had to close due to the Covid-19 pandemic. As one of the engineering programmes at UiTM Cawangan Pulau Pinang, Bachelor of Chemical Engineering Programme (EH225) has reviewed the delivery and assessment method to maintain the continuity of curriculum structures by the implementation of Open Distance Learning. This paper reviews the implementation of teaching delivery and assessment methods specifically for EH225 before and during MCO. The transition method needs to cater to all types of assessment including general courses, laboratory, capstones project especially final year projects and integrated design projects. Since the outcomes of the programmes cannot be compromised, setting an attainable benchmark aligns with expected learning needs that should be considered. In addition, the shift in the delivery and assessment associated with modern technology and online platforms promote a technology-enhanced learning approach to facilitate the improvement of the programmes' curriculum